TRAP sequence – A case of successful conservative management - Varejão, Ana (2024)
Twin reversed arterial perfusion (TRAP) is a rare sequence that complicates monochorionic multiple pregnancies. This condition affects both fetuses - the acardiac twin and the pump twin.  This report presents the case of a monochorionic multiple pregnancy complicated by TRAP diagnosed in the first trimester. After clarifying the couple and multidisciplinary discussion, conservative management was chosen because no genetic abnormalities or complications were identified in the normal twin development throughout pregnancy, and the acardiac twin stopped growing at 16 weeks, resulting in a vaginal term delivery of a healthy baby. In utero intervention is currently the first-line treatment option in these cases, but several studies have reported the benefits of an expectant approach. The optimal approach has not yet been established.